Climate Change Impacts on Sediment Yield and Debris‐Flow Activity in an Alpine Catchment. Issue 1 (23rd January 2021) - Hirschberg, Jacob; Fatichi, Simone; Bennett, Georgina L.; McArdell, Brian W.; Peleg, Nadav; Lane, Stuart N.; Schlunegger, Fritz; Molnar, Peter
Abstract: Climate change impacts on sediment production and transfer processes on hillslopes and through channels are governed by possible changes in precipitation, runoff, and air temperature. These hydrological and geomorphological impacts are difficult to predict in temperature‐sensitive Alpine environments. In this study, we combined a stochastic weather generator model with the most current climate change projections to feed a hillslope‐channel sediment cascade model for a major debris‐flow system in the Swiss Alps (the Illgraben). This allowed us to quantify climate change impacts and their uncertainties on sediment yield and the number of debris flows at hourly temporal resolution. We show that projected changes in precipitation and air temperature lead to a reduction in both sediment yield (−48%) and debris‐flow occurrence (−23%). This change is caused by a decrease in sediment supply from hillslopes, which is driven by frost‐weathering. Additionally, we conduct model experiments that show the sensitivity of projected changes in sediment yield and debris‐flow hazard to basin elevation, with important implications for assessing natural hazards and risks in mountain environments. Future changes in hydrological and sediment fluxes are characterized by high uncertainty, mainly due to irreducible internal climate variability. Therefore, this stochastic uncertainty needs to be considered in climate change impact assessments for geomorphic systems. Key Points: A chain of climate‐hydrology‐geomorphology models is used to quantify possible impacts of climate change on sediment yields and debris flows Future climate conditions favor increases in sediment‐transport capacity but a reduction in sediment supply limits debris‐flow activity A reduction in sediment yield of −48% is expected by 2085; predicted reductions in nearer future are within present‐day natural variability